Evodiamine inhibits migration and invasion by Sirt1-mediated post-translational modulations in colorectal cancer. Issue 6 (July 2019) - Zhou, Peng; Li, Xiao-Peng; Jiang, Rong; Chen, Yi; Lv, Xiao-Ting; Guo, Xing-Xian; Tian, Kuan; Yuan, De-Zhi; Lv, Yan-Wei; Ran, Jian-Hua; Li, Jing; Chen, Di-Long
Abstract : Colorectal cancer (CRC) is one of the most difficult cancers to cure. An important prognostic factor is metastasis, which precludes curative surgical resection. Recent evidences show that Evodiamine (EVO) exerts an inhibitory effect on cancer cell apoptosis, migration, and invasion. In this study, we investigated the effects of EVO on the metastasis of CRC cells in vitro and in vivo . In vitro, wound-healing and transwell assay showed that migration and invasion of HT-29 and HCT-116 CRC cells were inhibited significantly by EVO. Western blot and RT-PCR showed that EVO reduced the expression of matrix metalloproteinase-9 in a dose-dependent manner. In EVO-induced cells, the intracellular NAD+/NADH ratio was increased, the level of Sirt1 was increased, and acetyl-NF-κB P65 was decreased. This process was inhibited by nicotinamide, an inhibitor of Sirt1. In vivo, EVO reduced tumor metastasis markedly. These findings provide evidences that EVO suppresses the migration and invasion of CRC cells by inhibiting the acetyl-NF-κB p65 by Sirt1, resulting in suppression of metalloproteinase-9 expression in vitro and in vivo.